1995
DOI: 10.1172/jci117796
|View full text |Cite
|
Sign up to set email alerts
|

Human alveolar macrophages present antigen ineffectively due to defective expression of B7 costimulatory cell surface molecules.

Abstract: Alveolar macrophages, resident phagocytic cells in the lung that derive from peripheral blood monocytes, are paradoxically ineffective in presenting antigen to T cells. We found that antigen presentation by alveolar macrophages could be restored by the addition of anti-CD28 mAb to cultures of T cells and macrophages, indicating that costimulation by alveolar macrophages via the CD28 pathway was defective. In addition, we found that alveolar macrophages activated with IFN-y failed to express B7-1 or B7-2 antige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
94
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(103 citation statements)
references
References 42 publications
7
94
0
1
Order By: Relevance
“…Previous studies have suggested that alveolar macrophages are poor APCs, at least in part because they express little or no B7 costimulatory molecules (14,26). IL-10 is known to suppress LPSinduced B7 expression and cytokine synthesis by peripheral blood monocytes in vitro (16,27).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have suggested that alveolar macrophages are poor APCs, at least in part because they express little or no B7 costimulatory molecules (14,26). IL-10 is known to suppress LPSinduced B7 expression and cytokine synthesis by peripheral blood monocytes in vitro (16,27).…”
Section: Discussionmentioning
confidence: 99%
“…We used anti-CD3 as a mitogen because this stimulus had previously been shown to require costimulation via B7 (14). First, we compared the ability of BALMs with that of adherence purified splenic macrophages to provide costimulation with anti-CD3 Ab, using purified splenic T cells as the responders.…”
Section: Costimulatory Effect Of Balms For T Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…In two studies using AM isolated by BAL and evaluated by flow cytometry, normal AM were reported to be B7-1 ¹ and weakly positive for B7-2, and the expression of these costimulatory molecules was not increased by culture in the presence of IFN-g [14,15]. From these results, the authors suggested that the poor ability of AM to serve as accessory cells for antigen-induced T cell proliferation is due to defective expression of B7 molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, activation of DC is continuously attenuated by immunosuppressive cytokines 3 such as transforming growth factorb (TGFb). [4][5][6] TGFb belongs to a well-defined multi-potent cytokine family involved in many pathophysiological events. 7 Three isoforms (TGFb1, TGFb2 and TGFb3) that bear overlapping activities are expressed in mammals.…”
Section: Introductionmentioning
confidence: 99%